Multi-locus methylation analyses reveal GNAS methylation defects in three patients with the Beckwith–Wiedemann syndrome phenotype and no molecular defects in the 11p15.5 imprinted region - Tatsuki Urakawa; Yuri Kanamaru; Naoko Amano; Akira Uchida; Maki Fukami; Masayo Kagami (Clinical Epigenetics)
Abstract Background Beckwith–Wiedemann syndrome (BWS) is a congenital imprinting disorder (ID) caused by molecular defects in the 11p15.5 imprinted region, such as hypomethylation of the KCNQ1OT1:TSS-differentially methylated region (KCNQ1OT1-DMR) and hypermethylation of the H19/IGF2:IG-DMR, and maternal CDKN1C pathogenic variants, with various clinical characteristics, including overgrowth and macroglossia. Recently, the concept of Beckwith–Wiedemann spectrum (BWSp) and a clinical scoring system for BWS have been proposed, and cases with four or more points are diagnosed with classic BWS, and 20% of cases with BWS have no molecular defects in the 11p15.5 imprinted region. Pseudohypoparathyroidism type 1B (PHP1B, alias inactivating parathyroid hormone (PTH)/PTH-related protein signaling disorder 3) has characteristics of hormone resistance, particularly PTH, caused by methylation defects in DMRs at the GNAS locus (GNAS-DMRs). Some cases with PHP1B show postnatal overgrowth, which overlaps the BWS-phenotype. However, no studies have conducted a multi-locus methylation analysis for the ID-responsible DMRs other than the DMRs in 11p15.5 in cases with the BWS-phenotype and without molecular defects in the 11p15.5 imprinted region. Results We conducted methylation analysis using pyrosequencing in 77 patients showing the BWS-phenotype without molecular defects in the 11p15.5 imprinted region. Consequently, we identified three patients with methylation defects in the GNAS-DMRs. Patients 1, 2, and 3 had 9, 5, and 4 points in a BWSp score, respectively. All three patients had macroglossia and postnatal overgrowth. Further analyses, methylation-specific multiple ligation-dependent probe amplification for multiple DMRs, array-based methylation analysis, exome sequencing, array comparative genome hybridization analysis, and microsatellite marker analysis showed 9p deletion in Patient 1 and paternal uniparental isodisomy of chromosome 20 in Patient 2 together with multiple methylation defects in DMRs other than the GNAS-DMRs. Patient 3 had methylation defects in only the GNAS-DMRs. Conclusion Methylation defects in the GNAS-DMRs can cause the BWS-phenotype. For cases with the BWS-phenotype but no molecular defects in the 11p15.5 imprinted region, methylation analysis for the DMRs at the GNAS locus should be considered.